The Impact of Song and Picture Media on the Memory Ability of Elementary School Students in Science Subjects - Safitri, Mentari Nur; Minsih (International Journal of Elementary Education, 2022)
Science learning contains many material concepts that must be memorized and understood by participants. It's just that the reality on the ground shows that students' memory abilities are still relatively low, so students need media that can help improve their memory. The purpose of this research is to analyze the effect of song and picture media on the memory ability of elementary school students in science subjects. This research is a quantitative quasi-experimental research with a pretest-posttest design, using probability sampling technique as a sampling technique. The population in this study were all elementary school students. Sampling was carried out using probability sampling techniques and random sampling methods, so that the research sample obtained was 30 students of class V. Data collection in the study was carried out using the test and observation method. The research instrument used is in the form of posttest and pretest, each of which consists of 25 multiple choice questions. In addition, the teacher was observed using a teacher activity sheet that detailed every teacher's movement, from the preparation of tools and materials to the delivery of the material. The research data were then analyzed using the Data Homogeneity test, data normality test, and hypothesis testing with the help of the SPSS (Statistical Product and Service Solution) application. The results of the research analysis showed that the results of the pretest and posttest that experienced differences in the average value, namely the pretest score was 52.53 and the posttest was 93.60, which means that there is an effect of increasing memory ability in fifth grade elementary school students after using the media of songs and pictures.